Producer’s Responsibility Concerning the Assurance and Statement of Quality for Foods with “Organic Image” based on the Model of a Romanian Company - Magdalena Bobe; Roxana Procopie; Rodica Pamfilie; Maria Alexandra Toma (Amfiteatru Economic)
The responsibility of organizations to the consumer has now become a permanent concern, the principles of ethics in their activities result in attracting new customers and thus in their remaining within competition. The present study aims to highlight the importance of producers’ accountability in ensuring the quality of foodstuffs obtained through sustainable methods of production and to correctly and completely inform the consumers. The research follows the quality analysis of a product with an “organic image” addressed to the market/consumers, by testing the physicochemical and microbiological characteristics in the laboratory of the National Research and Development Institute for Food Bio- Resources in Bucharest, as well as comparing the obtained results with the values stated in the producer’s specifications; the main purpose is checking the conformity and establishing the validity of the published nutritional information and the statements regarding the product’s quality made on the printed label.